Fragmentierungen - Magen, Stefan (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2018)
This volume includes lectures and discussion from the Conference of the Association of German Professors of Constitutional Law in Saarbrücken, 4-7 October 2017